Rigid Occipitocervical Instrumented Fusion for Atlantoaxial Instability in an 18-Month-Old Toddler With Brachytelephalangic Chondrodysplasia Punctata: A Case Report. Issue 23 (1st December 2017) - Oba, Hiroki; Takahashi, Jun; Takano, Kyoko; Inaba, Yuji; Motobayashi, Mitsuo; Nishimura, Gen; Kuraishi, Shugo; Shimizu, Masayuki; Ikegami, Shota; Futatsugi, Toshimasa; Uehara, Masashi; Kosho, Tomoki; et al.
Abstract : Study Design: Case report. Objective: We report here on an 18-month-old boy with brachytelephalangic chondrodysplasia punctata (BCDP), whose atlantoaxial instability was successfully managed with occipitocervical instrumented fusion (OCF) using screw and rod instrumentations. Summary of Background Data: Recently, there have been a number of reports on BCDP with early onset of cervical myelopathy. Surgical OCF is a vital intervention to salvage affected individuals from the life-threatening morbidity. Despite recent advancement of instrumentation techniques, however, rigid OCF is technically demanding in very young children with small and fragile osseous elements. To our best knowledge, this is the first report on application of the instrumentation technique to a toddler patient with BCDP. Methods: A 16-month-old boy with BCDP presented with tetraplegia and swallow obstacle. Hypoplasia of the odontoid process and atlantoaxial instability were present in lateral radiographs. T2-weighted magnetic resonance (MR) images revealed a high signal region in the spinal cord at the C1-2 and C7-T1 levels. Cervical computed tomography (CT) showed that the pedicles and lateral masses in the cervical spine were small and immature, but the laminae were comparatively thick. Results: One week before surgery, the patient was fitted with a Halo-body jacket. We performed plate-rod placement with occipital cortical screws and C2/C3 interlaminar screws, and added an autogenous bone graft using the right 8 and 9 ribs. Rigid fixation of the occipito-cervical spine was completed successfully without major complications. Postoperative halo-body jacket immobilization was continued for 3 months, after which Aspen collar was fitted. CT confirmed occipitocervical bone fusion at 6 months after surgery. Mild clinical improvements in motor power of the affected muscles and swallowing were witnessed at 1 year postoperatively. Conclusion: Rigid fixation using screw, rod, and occipital plate instrumentation was successful in an 18-month-old toddler with BCDP and atlantoaxial instability. Bone fusion was achieved at postoperative 6 months. Level of Evidence: 5